Nucleophilic Phosphine-Promoted Domino Reaction of Dialkyl Acetylenedicarboxylates and 3-Arylamino-1-methyl-1H-pyrrole-2,5-diones - Liu, Chang-Zhou; Han, Ying; Zhang, Yuan-Yuan; Sun, Jing; Yan, Chao-Guo (Synthesis, 2018)
The three-component reaction of triphenylphosphine, dimethyl acetylenedicarboxylate and 3-arylamino-1-methyl-1H-pyrrole-2,5-diones in CH2Cl2 at room temperature resulted in functionalized 3-(triphenyl-λ5-phosphanylidene)succinates in nearly quantitative yields. However, tri(n-butyl)phosphine promoted reaction of dialkyl acetylenedicarboxylates and 3-arylamino-1-methyl-1H-pyrrole-2,5-diones in CH2Cl2 afforded functionalized pyrrolo[3,4-b]pyridine-4-carboxylates in satisfactory yields.
Keywords: phosphine; electron-deficient alkyne; pyrrolo[3,4-b]pyridine; β-enamino amides; multicomponent reaction